2018
DOI: 10.3389/fimmu.2018.01960
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation With ω6 LC-PUFA-Rich Algae Modulates Zebrafish Immune Function and Improves Resistance to Streptococcal Infection

Abstract: Arachidonic acid (ARA, 20:4n-6) and dihomo-γ-linolenic acid (DGLA, 20:3n-6) are omega-6 long-chain polyunsaturated fatty acids (LC-PUFA), which are key precursors for lipid mediators of the immune system and inflammatory response. The microalga Lobosphaera incisa (WT) and its Δ5-desaturase mutant P127 (MUT) are unique photosynthetic sources for ARA and DGLA, respectively. This study explores the effect of dietary supplementation with L. incisa and P127 biomass on tissue fatty acid composition, immune function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 78 publications
5
34
1
Order By: Relevance
“…More studies have shown that feeding zebrafish microalgae rich diets can lead to gene expression changes in the liver. Microalgae supplements containing a species rich in arachidonic acid (ARA) lead to upregulation of immune system-related genes and antioxidant defense (Nayak et al, 2018) in contrast to our study where we saw mostly downregulation. EPA and DHA are known to have anti-inflammatory effects, whereas ARA is known to be pro-inflammatory, which can be part of the explanation for the differential responses.…”
contrasting
confidence: 99%
“…More studies have shown that feeding zebrafish microalgae rich diets can lead to gene expression changes in the liver. Microalgae supplements containing a species rich in arachidonic acid (ARA) lead to upregulation of immune system-related genes and antioxidant defense (Nayak et al, 2018) in contrast to our study where we saw mostly downregulation. EPA and DHA are known to have anti-inflammatory effects, whereas ARA is known to be pro-inflammatory, which can be part of the explanation for the differential responses.…”
contrasting
confidence: 99%
“…Here, we demonstrated that DGLA administration in several forms modulated the immune response in RAW264.7 macrophages. While this work was confined to a cell model, the results further support the anti-inflammatory and immunomodulatory potential of the L. incisa-derived DGLA, previously demonstrated in zebrafish feeding trials [23,63]. Additional studies are required to translate these findings to the use of DGLA as feed and health-promoting food supplements for conditions and pathologies that are caused by imbalance in the immune system.…”
Section: Discussionsupporting
confidence: 78%
“…This ability is rarely encountered in microalgal lineages and absent from land plants. The delta-5 desaturase mutant of L. incisa P127, deficient in ARA, represents a prospective oleaginous organism for the photosynthesis-driven biotechnological production of DGLA for dietary and medicinal applications [7,23]. It accumulates up to 30% of DGLA in storage lipids, triacylglycerols, under nitrogen starvation conditions [24].…”
Section: Introductionmentioning
confidence: 99%
“…An optimal amount of ARA is necessary for growth, survival, and immune function, while an overdose may have negative impacts as result of inflammation associated with eicosanoid production. In our previous study, zebrafish fed with diets supplemented with the omega-6 LC-PUFA-rich oleaginous green microalga Lobosphaera incisa-either ARA-rich wild-type (WT) or DGLA-rich mutant (MUT) strains-resulted in significant incorporation of the respective fatty acids in the gut [24] and liver [25]. Dietary supplementation also improved immune function and enhanced resistance to Streptococcus iniae infection [25].…”
Section: Introductionmentioning
confidence: 98%
“…In our previous study, zebrafish fed with diets supplemented with the omega-6 LC-PUFA-rich oleaginous green microalga Lobosphaera incisa-either ARA-rich wild-type (WT) or DGLA-rich mutant (MUT) strains-resulted in significant incorporation of the respective fatty acids in the gut [24] and liver [25]. Dietary supplementation also improved immune function and enhanced resistance to Streptococcus iniae infection [25]. However, the possible association of this immunomodulatory effect with alterations in the fish gut microbiota is poorly understood.…”
Section: Introductionmentioning
confidence: 99%